SOSIALISASI PENGGUNAAN WEBSITE DESA KOLABORASI ANTARA TIM KKN UMSIDA DAN PEMERINTAHAN DESA SEDAENG: SOSIALISASI PENGGUNAAN WEBSITE DESA KOLABORASI ANTARA TIM KKN UMSIDA DAN PEMERINTAHAN DESA SEDAENG - Tirtoni, Feri; Ahmad Nurefendi; Kandina Bahagia; Aura Rafiqa (Kanigara, 2026)
In today's digital era, websites have become an important element in everyday life, serving as a means to find information, communicate, do business, and entertainment. This research aims to evaluate the quality of website services and propose the creation of a village website as an information medium to increase public understanding of Village-Owned Enterprises (BUMDes) in Sedaeng Village. The research method used is descriptive qualitative, with data collection through observation, literature study, and application of the Waterfall method in website development. The results showed that collaboration between KKN-P students and village officials in website development can improve transparency,